Prudential bank regulation: a post-Keynesian perspective. Issue 3 (November 2020) - Docherty, Peter
Abstract : Banks play an important role in the post-Keynesian theory of endogenous money but post-Keynesians have not paid much attention to the prudential regulation of banks. Do post-Keynesian insights into the role of banks cast any light on the way they ought to be regulated, or can the conventional treatment of prudential bank regulation be grafted onto post-Keynesian theory without any significant modification? This paper begins a process of reflection on these questions. It argues that conventional prudential regulation theory can be utilised by post-Keynesians but with important modifications including a renewed emphasis on liquidity and greater recognition of endogenously generated systemic risk. A post-Keynesian approach to prudential bank regulation is shown to be characterised by both liquidity and capital requirements, as well as by a macroprudential framework that facilitates the counter-cyclical adjustment of these requirements in response to endogenous variations in systemic risk.